A PTFE / modified polyimide composite membrane with high temperature bonding performance and its preparation method and application

By applying FPAA glue and PTFE resin to the PI film, a PTFE/modified polyimide composite film with high temperature binding properties was prepared, which solved the problem of easy peeling of existing PI/PTFE composite materials in high temperature environments, and achieved the stable performance of the composite film in high temperature and chemical corrosion environments.

CN117887124BActive Publication Date: 2025-03-04WUXI SHUNXUAN NEW MATERIALS +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410043259.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-11
Publication Date
2025-03-04
Estimated Expiration
2044-01-11

AI Technical Summary

Technical Problem

The existing PI/PTFE composite materials are easily peeled off in high temperature environments, which limits their application in special cables and other fields.

Method used

By applying FPAA glue to the surface of the PI film and applying PTFE resin to the surface of the modified polyimide film, drying and curing, a PTFE/modified polyimide composite film with high temperature binding properties was prepared.

Benefits of technology

The composite film is not easy to peel off under multiple heating conditions and has strong bonding power. It is suitable for high temperature and chemical corrosion resistance environments, and is suitable for special cables and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117887124B_ABST
    Figure CN117887124B_ABST
Patent Text Reader

Abstract

The invention discloses a PTFE / modified polyimide composite film with high temperature bonding performance, a preparation method and application thereof, and belongs to the technical field of polyimide films. The method comprises coating FPAA glue on the surface of a PI film to obtain a multilayer modified polyimide film, and then coating PTFE resin on the surface of the multilayer modified polyimide film, drying, and curing to obtain a PTFE / modified polyimide composite film; the FPAA glue is prepared from aromatic diamine and aromatic dianhydride. The FPAA of the invention has good bonding with PTFE and can replace FEP as a functional layer bonded to PTFE. The PTFE and modified polyimide of the prepared composite film have the advantage of not peeling off after multiple heating, and can be applied to special environment fields such as high temperature resistance, chemical corrosion resistance, and special cable preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a PTFE / modified polyimide composite film with high-temperature bonding performance, a preparation method and application thereof. Background Art

[0002] Polyimide (PI for short) refers to a class of polymers containing imide rings on the main chain. According to the different types of alkyl groups on the main chain, it is divided into aliphatic polyimide and aromatic polyimide. Among them, aromatic PI containing benzene rings on the main chain has been the focus of researchers because of its excellent thermal stability, good mechanical properties, chemical stability, radiation resistance, non-toxicity and good dielectric properties. Due to its excellent performance, PI plays an important role in various high-tech fields as an important matrix of comprehensive engineering plastics and composite materials. At present, as the application field of PI gradually expands, there are more than 60 companies producing PI in the world, among which the more famous manufacturers include Do Pont, Amoco, General Electric in the United States, BASF and Ciba Geigy in Europe, DuPont-Toray, Asahi Chemical Industry, Synthetic Rubber Company, Nissan Chemical, Ube Industries, Hitachi Chemical, Sumitomo Chemical, Toray Industries, etc. in Japan. In order to meet the needs of national defense, my country also started the development and research of PI in 1962. In the 1980s, driven by the national economy, PI films developed rapidly. Several major types of PI have been developed in China, such as benzene type, partial anhydride type, ketone anhydride type, monoether type, biphenyl dianhydride type and bisphenol A dianhydride type, and they have all been initially applied. The imide ring in PI gives it excellent performance, and the more stable aromatic heterocyclic structure in aromatic PI makes the performance of aromatic PI more outstanding, such as excellent mechanical properties, good chemical stability, high temperature resistance, radiation resistance and electrical properties. Although PI has excellent comprehensive properties, there are still many shortcomings. Aromatic PI contains benzene ring and imide ring structure. Due to electronic polarization and molecular crystallinity, the molecular chains are closely arranged, resulting in the shortcomings of PI being insoluble, non-melting, difficult to process, high molding pressure and high reaction temperature, which limits the application of PI. For example, due to the high reaction temperature of aromatic PI, the transparency of the prepared material is not high, which affects its application in the field of microelectronics industry. Therefore, modification of PI has become a research hotspot. Currently, the main modifications of PI include structural improvement, blending modification, copolymerization modification and filling modification.

[0003] Structural modification is to modify the structure of PI, such as introducing flexible segments, twisted and non-coplanar structures, hyperbranched structures, and functional side groups, and adjusting the ratio of flexible segments to rigid segments in the polymer to improve the performance of PI. Copolymerization modification is to condense diamine and dianhydride in a non-protonic polar solvent (such as DMF, DMAC, NMP) to synthesize polyamic acid, and then undergo imidization treatment to generate PI. Blending modification is to blend polyamic acid (BPDA-PRM PAA) and polyamic acid (BPDA-ODA PAA), prepare PI nanofibers by electrospinning technology, and then perform imidization. Composite modification is to use PI as the base material and fill various fillers according to the requirements of the composite material.

[0004] Polytetrafluoroethylene (PTFE), trade name "Teflon", is commonly known as the "King of Plastics". In 1938, American scientist R.S. Splunket first synthesized PTFE and commercialized it in 1946. PTFE is a polymer of tetrafluoroethylene (TFE). It is a polymer with a highly symmetrical, unbranched linear structure. It is white and non-toxic. It is a new type of engineering polymer material. The PTFE molecular chain is formed by carbon-fluorine atoms through covalent bonds, and the adjacent fluorine atoms repel each other due to the charge, so that the CC bond changes from the original planar, fully extended conformation to a helical conformation, and the outer fluorine atoms give PTFE a fully "fluorinated" protective layer. This feature makes PTFE have stable chemical corrosion resistance. The bond energy of the CC bond in the PTFE molecular chain is 332kJmol-1, and the bond energy of the CF bond is 485kJmol-1, which gives PTFE good heat resistance and can be used for a long time at high temperatures. Because PTFE has a highly symmetrical structure, it not only has stable thermal properties and chemical corrosion resistance, but also has advantages such as low dielectric constant, low surface energy, and low friction coefficient. The "fluorinated" helical structure, the highly symmetrical molecular chain, and the electronegativity of fluorine atoms make PTFE have advantages such as excellent thermal stability, chemical corrosion resistance, ultra-low surface energy, low dielectric properties, lubricity, and anti-adhesion, and has been widely used in materials, chemical industry, medicine, food industry, and aerospace industries. However, due to the unique helical structure and the highly symmetrical molecular structure, it has some inherent defects, such as ultra-high melt viscosity, poor dissolution, poor heat transfer performance, and difficult molding processing, which greatly limit its application. Therefore, many scholars currently modify and compound PTFE to improve the comprehensive performance of composite materials and broaden the application of PTFE in different fields.

[0005] Perfluoroisopropylene (F46 or FEP) is a copolymer of tetrafluoroethylene and hexafluoropropylene, and has excellent processing properties and electrical insulation properties. However, FEP is easy to crack, and its stress cracking resistance is generally directly related to the molecular weight of the polymer. Products with high molecular weight generally have stronger stress resistance, but are not suitable for high-speed processing. FEP resins with low molecular weight and wide molecular weight distribution have poor stress cracking resistance, wear resistance and creep resistance are also lower than many engineering plastics, and its thermal stability and mechanical properties are relatively poor, so FEP is often used in combination with other materials.

[0006] When molding FEP / PI composite film, FEP cannot melt at a low temperature, so it is easy to break after molding. The strength of the molded composite material is very low, and it may even break during the molding process. As the temperature rises, the degree of mixing of FEP and PI increases, but when the temperature exceeds 260°C, the strength of the composite material decreases, and the two will peel off, so it cannot be widely used.

[0007] Both PI and PTFE are polymer materials with excellent performance, such as outstanding thermal stability, chemical resistance, radiation resistance, etc. At the same time, PTFE also has the characteristics of low dielectric constant, low surface energy, lubricity, etc. However, its inherent disadvantages, such as ultra-high melt viscosity and difficulty in solubility, greatly limit its application. Combining the advantages of PI, researchers began to invest their research direction in PI / PTFE composite materials, combining the advantages of both, making up for the shortcomings, and preparing polymer materials that better meet the requirements of modern science and technology. At present, the research on PI / PTFE composite materials has achieved certain results, but it is mainly focused on the friction and wear, separation performance, and sensing materials of PI / PTFE composite materials. Although the PI / PTFE composite membrane with low dielectric constant has good thermal and mechanical properties, as the PTFE content increases, PTFE agglomeration occurs; PI / PTFE composite materials are easier to peel off; PI / PTFE composite nanofiber membrane with super hydrophobicity, due to long-term electrospinning, polyamic acid salt degrades, affecting the mechanical properties of PI / PTFE composite nanofibers.

[0008] PI is widely used in electronic circuit boards, displays, semiconductors, aerospace, new energy, medical, military and other fields due to its excellent mechanical properties, heat resistance, weather resistance, electrical insulation, flame retardancy and other properties; PTFE is resistant to high temperature, corrosion, has excellent electrical insulation, aging resistance, low water absorption and other excellent properties, and is widely used in electrical, chemical, aerospace, mechanical and other fields. However, polyimide has high moisture absorption and is not alkali-resistant; PTFE has poor mechanical properties and becomes soft in high temperature environments; compounding PI and PTFE can effectively combine the advantages of both. The composite material has the advantages of acid and alkali resistance, weather resistance, high temperature resistance, arc resistance, etc. It is widely used in special environments such as aviation cables, semiconductor processes, wind power generation, etc. However, the extremely low surface energy of PTFE makes it very easy to peel off after combining with PI. Therefore, in order to improve the peeling resistance, it is necessary to adjust the PI structure to have better bonding with PTFE.

[0009] With the rise of industries such as rail transit, aerospace and shipbuilding, the demand for special cables has greatly increased. At present, the problem that PI / PTFE composite materials are used in the field of special cable preparation to solve is fire resistance and high temperature resistance, and the peeling resistance is not considered. In the high temperature environment where special cables are used, the existing PI / PTFE composite materials are resistant to high temperatures, but they are easy to peel off, resulting in damage and unusability.

[0010] Therefore, it is urgent to improve the peeling performance of PI / PTFE composite membranes. Summary of the invention

[0011] In view of the above problems existing in the prior art, the first technical problem to be solved by the present invention is to provide a method for preparing a PTFE / modified polyimide composite membrane with high temperature bonding performance, and to prepare a PTFE / modified polyimide composite membrane with high temperature bonding performance. The second technical problem to be solved by the present invention is to provide a PTFE / modified polyimide composite membrane with high temperature bonding performance, which has the performance of not peeling off after multiple heating and good bonding strength. The third technical problem to be solved by the present invention is to provide a PTFE / modified polyimide composite membrane with high temperature bonding performance for use in high temperature resistant environment, chemical corrosion resistant environment and special cable preparation field.

[0012] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0013] A method for preparing a PTFE / modified polyimide composite membrane with high-temperature bonding performance comprises the following steps: coating FPAA (fluorinated polyamic acid) glue on the surface of a PI film to obtain a modified polyimide membrane, and then coating PTFE resin on the surface of the modified polyimide membrane, drying, and curing to obtain the PTFE / modified polyimide composite membrane; the FPAA glue is prepared from aromatic diamines and aromatic dianhydrides, the aromatic diamines are selected from 4,4'-diaminodiphenyl ether and 2,2'-di(trifluoromethyl)diaminobiphenyl; the aromatic dianhydrides are selected from 3,3',4,4'-biphenyltetracarboxylic dianhydride and 4,4'-(hexafluoroisopropyl)diphthalic anhydride.

[0014] The method for preparing the PTFE / modified polyimide composite membrane with high temperature bonding performance comprises the following specific steps:

[0015] 1) dissolving an aromatic diamine in an organic solvent, mixing well, and then adding an aromatic dianhydride to react to obtain FPAA glue;

[0016] 2) coating the FPAA glue prepared in step 1) onto the surface of the PI film to obtain a multilayer modified polyimide film, wherein the thickness of the multilayer modified polyimide film is 2 to 5 μm;

[0017] 3) coating the surface of the multilayer modified polyimide membrane prepared in step 2) with PTFE resin, drying it, and curing it at 370-390° C. to obtain a PTFE / modified polyimide composite membrane.

[0018] In step 1), the aromatic diamine is a mixture of 4,4'-diaminodiphenyl ether and 2,2'-bis(trifluoromethyl)diaminobiphenyl.

[0019] The amount of the 2,2'-bis(trifluoromethyl)diaminobiphenyl used is more than 20% of the total molar amount of the aromatic diamine.

[0020] In step 1), the aromatic dianhydride is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and / or 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0021] The amount of 3,3',4,4'-biphenyltetracarboxylic dianhydride used is more than 50% of the total molar amount of aromatic dianhydride.

[0022] In step 1), the organic solvent is N,N-dimethylacetyl and / or N-methylpyrrolidone, and the amount of the organic solvent used is 75-90% of the total mass of the aromatic diamine and the aromatic dianhydride.

[0023] In step 3), the PTFE resin coating has a thickness of 2 to 20 μm.

[0024] The method prepares a PTFE / modified polyimide composite membrane with high-temperature bonding performance.

[0025] The PTFE / modified polyimide composite film with high temperature bonding performance is used in the fields of high temperature resistant environment, chemical corrosion resistant environment and special cable preparation.

[0026] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0027] (1) The composite membrane prepared by the present invention is composed of a multilayer composite of polyimide / modified polyimide film / PTFE, and the polyimide film used is a mechanical support layer, which has good support performance.

[0028] (2) The modified polyimide film layer of the composite membrane prepared by the present invention has a high bonding strength with the polyimide layer and the PTFE layer, and has the property of not peeling off after multiple heating.

[0029] (3) The PTFE layer of the composite membrane prepared by the present invention has a chemical corrosion resistance function and can be used in a chemical corrosion resistant environment.

[0030] (4) The three-layer interface of the composite membrane prepared by the present invention is well bonded and has good comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A cross-sectional view of the PTFE / modified polyimide composite membrane prepared by the present invention;

[0032] Figure 2 This is a cross-sectional view of the double-sided PTFE / modified polyimide composite membrane prepared in the present invention. DETAILED DESCRIPTION

[0033] The present invention is further described below in conjunction with specific embodiments.

[0034] Example 1

[0035] (1) Aromatic diamine 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB) is mixed and stirred in an organic solvent N,N-dimethylacetamide (DMAC) to dissolve, and aromatic dianhydride 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) is added and stirred to react. After stirring for 5 hours, a fluorinated polyamic acid glue having a viscosity of 45100 cp is obtained; wherein the molar ratio of TFMB to s-BPDA is 1:0.996, and the amount of DMAC used is 82% of the total mass of TFMB and s-BPDA.

[0036] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0037] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0038] Example 2

[0039] (1) Aromatic diamine TFMB is mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA) is added and stirred for reaction. After reacting for 1 hour, aromatic dianhydride s-BPDA is added and stirred for 5 hours to obtain a fluorinated polyamic acid glue with a viscosity of 44300cp; wherein the molar ratio of s-BPDA to 6FDA is 8:2, the molar ratio of aromatic diamine to aromatic dianhydride is 1:0.996, and the amount of DMAC used is 82% of the total mass of TFMB, 6FDA and s-BPDA.

[0040] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0041] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0042] Example 3

[0043] (1) Aromatic diamine TFMB is mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride 6FDA is added and stirred to react. After reacting for 1 hour, aromatic dianhydride s-BPDA is added and stirred for 5 hours to obtain a fluorinated polyamic acid glue with a viscosity of 43600cp; wherein the molar ratio of s-BPDA to 6FDA is 1:1, the molar ratio of aromatic diamine to aromatic dianhydride is 1:0.996, and the amount of DMAC used is 82% of the total mass of TFMB, 6FDA and s-BPDA.

[0044] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0045] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0046] Example 4

[0047] (1) Aromatic diamine TFMB is mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride 6FDA is added and stirred to react. After reacting for 1 hour, aromatic dianhydride s-BPDA is added and stirred for 5 hours to obtain a fluorinated polyamic acid glue with a viscosity of 41500cp; wherein the molar ratio of s-BPDA to 6FDA is 2:8, the molar ratio of the mixed solution of aromatic diamine and aromatic dianhydride is 1:0.997, and the amount of DMAC used is 82% of the total mass of TFMB, 6FDA and s-BPDA.

[0048] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0049] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0050] Example 5

[0051] (1) Aromatic diamine TFMB was mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride 6FDA was added and stirred to react. After stirring for 5 hours, a fluorinated polyamic acid glue having a viscosity of 39100 cp was obtained; wherein the molar ratio of TFMB to 6FDA was 1:0.997, and the amount of DMAC used was 82% of the total mass of TFMB and 6FDA.

[0052] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0053] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0054] Example 6

[0055] (1) Aromatic diamine TFMB and 4,4'-diaminodiphenyl ether (ODA) are added to an organic solvent DMAC, mixed and stirred to dissolve, and then aromatic dianhydride s-BPDA is added. After stirring for 5 hours, a fluorinated polyamic acid glue having a viscosity of 39500cp is obtained; wherein the molar ratio of TFMB to ODA is 8:2, the molar ratio of aromatic diamine to aromatic dianhydride is 1:0.996, and the amount of DMAC used is 82% of the total mass of TFMB, ODA and s-BPDA.

[0056] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0057] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0058] Example 7

[0059] (1) Aromatic diamine TFMB and ODA are mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride s-BPDA is added and stirred for 5 hours to obtain a fluorinated polyamic acid glue with a viscosity of 49800cp; wherein the molar ratio of TFMB to ODA is 1:1, the molar ratio of aromatic diamine to aromatic dianhydride is 1:0.996, and the amount of DMAC used is 82% of the total mass of TFMB, ODA and s-BPDA.

[0060] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0061] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0062] Example 8

[0063] (1) Aromatic diamine TFMB and ODA are mixed and stirred in an organic solvent DMAC to dissolve, and then aromatic dianhydride s-BPDA is added and stirred for 5 hours to obtain a fluorinated polyamic acid glue with a viscosity of 50800cp; wherein the molar ratio of TFMB to ODA is 2:8, the molar ratio of aromatic diamine to aromatic dianhydride is 1:0.994, and the amount of DMAC used is 82% of the total mass of TFMB, ODA and s-BPDA.

[0064] (2) The polyamic acid glue solution is coated on the polyimide film and dried at 180° C. for 7 min to obtain a modified polyimide composite film.

[0065] (3) PTFE is coated on the modified polyimide composite membrane, dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / PI composite modified polyimide composite membrane.

[0066] Example 9

[0067] Based on the principle of preparing the modified polyimide composite membrane of PTFE / PI composite in Examples 1 to 8, FPAA and PTFE were coated on both sides of the PI membrane to prepare a double-sided PTFE / PI composite modified polyimide composite membrane. The structural cross-sectional view of the composite membrane is shown in FIG. Figure 2 shown.

[0068] Comparative Example 1

[0069] The surface of the polyimide film prepared by the common polyimide (ODA / PMDA) system production line is coated with PTFE, dried in an oven at 180°C, and then cured in an oven at 370°C to 390°C to obtain a PTFE / PI composite polyimide film.

[0070] Comparative Example 2

[0071] FEP is coated on the PI film and dried in an oven at 180°C, and then PTFE is coated on the dried FEP / PI and dried in an oven at 180°C, and then put into an oven at 370°C to 390°C for curing to obtain a PTFE / FEP / PI composite film.

[0072] The bonding performance test of PTFE and PI of the composite membranes prepared in Examples 1 to 8, Comparative Examples 1 and 2 was expressed by peeling performance, wherein the bonding performance test method was as follows: after the composite membrane was subjected to a high temperature of 350°C, it was cooled to room temperature, and the operation was repeated, and finally the PI layer and the PTFE layer of the PTFE / PI composite modified polyimide composite membrane were manually torn apart at room temperature, and the number of repeated temperature rises and falls was recorded. The results are shown in Table 1 below.

[0073] Table 1 Performance test of composite membranes prepared in Examples 1 to 8, Comparative Example 1 and Comparative Example 2

[0074]

[0075]

[0076] Table 1 is a performance test of the composite membranes prepared by Examples 1 to 8, Comparative Example 1 and Comparative Example 2. It can be seen from the table that the modified polyimide layer of the composite membranes prepared by Examples 1 to 8 can have a good bonding force with PTFE and cannot be peeled off, while Comparative Example 1 and Comparative Example 2 are very easy to peel off under ordinary systems, and the composite membrane prepared by the present invention also has good mechanical properties.

Claims

1. A method for preparing a PTFE / modified polyimide composite membrane with high temperature bonding performance, characterized in that: FPAA glue is coated on the surface of the PI film to obtain a modified polyimide film, and then PTFE resin is coated on the surface of the modified polyimide film, dried, and cured to obtain a PTFE / modified polyimide composite film; the FPAA glue is prepared from aromatic diamines and aromatic dianhydrides; when the aromatic diamine is 2,2'-di(trifluoromethyl)diaminobiphenyl, the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride and / or 4,4'-(hexafluoroisopropyl)diphthalic anhydride; the aromatic diamine is 2,2'-di(trifluoromethyl)diaminobiphenyl and 4,4'-diamino When the aromatic dianhydride is a mixed solution of diphenyl ether, the aromatic dianhydride is 3,3',4,4'-biphenyltetracarboxylic dianhydride; when the aromatic dianhydride is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, the amount of 3,3',4,4'-biphenyltetracarboxylic dianhydride is 50% to 80% of the total molar amount of the aromatic dianhydride; when the aromatic diamine is a mixed solution of 2,2'-bis(trifluoromethyl)diaminobiphenyl and 4,4'-diaminodiphenyl ether, the amount of 2,2'-bis(trifluoromethyl)diaminobiphenyl is 50% to 80% of the total molar amount of the aromatic diamine; The specific preparation steps of the composite film are as follows: 1) Dissolve the aromatic diamine in an organic solvent, mix well, and then add aromatic dianhydride to react to obtain FPAA glue; 2) coating the FPAA glue prepared in step 1) onto the surface of the PI film to obtain a multilayer modified polyimide film, wherein the thickness of the multilayer modified polyimide film is 2 to 5 μm; 3) coating the surface of the multilayer modified polyimide membrane prepared in step 2) with PTFE resin, drying it, and curing it at 370-390° C. to obtain a PTFE / modified polyimide composite membrane.

2. The method for preparing a PTFE / modified polyimide composite membrane having high temperature bonding performance according to claim 1, characterized in that: In step 1), the organic solvent is N,N-dimethylacetyl and / or N-methylpyrrolidone, and the amount of the organic solvent used is 75-90% of the total mass of the aromatic diamine and the aromatic dianhydride.

3. The method for preparing the PTFE / modified polyimide composite membrane with high temperature bonding performance according to claim 1, characterized in that: In step 3), the PTFE resin coating has a thickness of 2 to 20 μm.

4. A PTFE / modified polyimide composite membrane having high temperature bonding performance prepared by the method according to any one of claims 1 to 3.

5. Application of the PTFE / modified polyimide composite film with high temperature bonding performance as claimed in claim 4 in the fields of high temperature resistant environment, chemical corrosion resistant environment and special cable preparation.

Citation Information

Patent Citations

  • Polyimide composite film as well as preparation method and application thereof

    CN113035470A

  • Polyimide composite film for special cable and preparation method thereof

    CN113831570A

  • Polyimide / polytetrafluoroethylene composite material and preparation method thereof

    CN114891259A